Effectiveness of Project-Based Learning to Improve Students Ability to Solve Problems - Azizahwati, Azizahwati; Islami, Nur; Putri, Tesa Liantika (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study is to assess the effectiveness of student solving abilities through the use of project-based learning.This study has used quasi experiments with the design of nonequivalent control group design.Instruments of the study using a student-solving ability test consisting of pretest and posttest, were analyzed using a quantitative approach. Inferential analysis using independent-sample t-test has shown that there is a significant difference in students ability to solve between the treatment class and the control class. It can thus be concluded that the use of project-based learning can improve student solving abilities on static fluid topics.